New portable device for an examination of visual cognitive evoked potentials might extend their diagnostic applications in psychiatry - Kuba, Miroslav; Kremláček, Jan; Vít, František; Masopust, Jiří; Hubeňák, Jan; Kubová, Zuzana; Szanyi, Jana; Ramešová, Lenka; Chutná, Marie; Langrová, Jana (Psychiatry research. Neuroimaging, 2024)
Despite positive prior results obtained by using event-related potentials (ERPs) in psychiatric patients, they are not routinely used in the clinical setting. This may in part be due to problems regarding a lack of transportable equipment availability. It can be difficult for these patients to repeatedly visit electrophysiological laboratories. To address this issue, we propose using a new, fully portable device for visually evoked potentials (VEP) and cognitive function assessment, that can be used for quick examinations (https://www.veppeak.com). Our device, called "VEPpeak", is built into a headset with a color LED visual stimulator. It weighs 390 g and is connected to a notebook (PC) with evaluation software via USB. In this pilot study, we verified the device's usability in 31 patients with schizophrenia. We used the oddball paradigm with the recognition of colors for the P300 wave and choice reaction time evaluation. The examination lasted only about ten minutes. The results indicated good reproducibility of large cognitive potentials (P300) with prolonged P300 latencies and reduced amplitudes in patients compared to 15 control subjects. The P300 latency and reaction time prolongation in patients correlated with their age and the sedative effect of the pharmacotherapy.
Keywords: Event related potentials; kognitivní evokované potenciály P300; Pilot Projects; Humans; P300 monitoring; reprodukovatelnost výsledků; ERP; kognice; Evoked Potentials; evokované potenciály; VEPpeak; psychiatrie; Psychiatry; Cognition; lidé; Reproducibility of Results; Schizophrenia; pilotní projekty; Event-Related Potentials, P300